META-ANALYSIS: ENHANCING JUNIOR HIGH SCHOOL STUDENTSâ€™ HIGHER ORDER THINKING SKILLS THROUGH PROBLEM SOLVING LEARNING MODEL IN NATURAL SCIENCES-PHYSICS - Sugianto, Rian; Permana P, Niki Dian; Diniya, Diniya (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
Â This research aims to analyze the application of problem solving learning models to improve students' higher-order thinking skills in science-physics learning. This research was conducted using a meta-analysis method. The steps taken are collecting scientific articles from accredited national journals in Sinta 1 to Sinta 4 relating to research topics, grouping journal articles, and analyzing data obtained descriptively. Based on the results of the analysis it was concluded that the application of the problem solving learning model can improve student learning outcomes by an average of 55.45 in the medium category. For the group of articles with the dependent variable creative thinking skills, critical thinking skills, science process skills, problem solving skills and metacognition abilities, all of which are classified as higher order thinking skills, an average increase of 56.65 in the medium category.